Financial programming and policy : the case of Turkey - Barth, Richard C. (Richard Carl), 1938-; Hemphill, William Loehr, 1941-; Aganina, Irina; George, Susan; Greene, Joshua E.; McNeilly, C. (Caryl); Paljarvi, Jukka (IMF Institute, International Monetary Fund, 2000)
The art of financial programming is a central element in the design of IMF-supported macroeconomic adjustment programs. This volume, edited by Richard Barth and William Hemphill, includes contributions from staff members of the IMF institute and introduces the reader to the concepts and tools of analysis needed to formulate a financial program. The book presents a series of workshops that explain the accounting identities, behavioral relationships, and forecasting techniques that underlie the construction of a financial program. The workshops use the case of Turkey to illustrate the techniques.